Staged buccal mucosa urethroplasty in reoperative hypospadias - Nerli, R. B. (Medknow Publications, 2011)
INTRODUCTION: Repeated attempts at surgical repair of serious complications involving either the partial or complete breakdown of the hypospadias repair are less likely to succeed because the penis is densely scarred, or significantly shortened, and the skin over the penis is immobile and hypovascular. Buccal mucosa (BM) has become the preferred material for reconstruction, whenever a child with skin-deficient hypospadias needs reoperation. We report the results of our surgical experience with staged reoperation using BM, in the repair of hypospadias in children with complications after multiple failed repairs. MATERIALS AND METHODS: Children needing reoperation for hypospadias underwent a staged repair using buccal mucosa. The complications were noted. RESULTS: Twenty-one children aged 3 – 16 years underwent this staged repair during the period May 2000 – April 2010. Two of these 21 children had a failed first stage. One child developed a urethro-cutaneous fistula following the second stage, which was corrected in an additional stage. CONCLUSIONS: The use of the buccal mucosa graft for urethral reconstruction in a child with hypospadias, needing a reoperation, is a successful method, with a low incidence of complications.